Atmospheric corrosion of fire-gilded bronze: corrosion and corrosion protection during accelerated ageing tests. (November 2015) - Chiavari, C.; Bernardi, E.; Balbo, A.; Monticelli, C.; Raffo, S.; Bignozzi, M.C.; Martini, C.
Highlights: Fire-gilded bronze (analogous to Lorenzo Ghiberti's Paradise Door, Florence, 1452) Corrosion rate decreases with time in electrochemical tests during wet&dry exposure Accelerated ageing in runoff/stagnant conditions (synthetic acid rain) induces corrosion at the gold/bronze interface Severe corrosion in runoff conditions, with morphology comparable to reference historical fire-gilded bronzes Organosilane coating on gilded bronze limits mass decrease and Cu release Abstract: Fire-gilded bronze (replicating the materials of Lorenzo Ghiberti's Paradise Door (Baptistery of Florence, 1452)) was aged in runoff/stagnant conditions by accelerated exposure tests in synthetic acid rain. After preliminary electrochemical investigations, a detailed characterization of gilded bronze samples before and after artificial ageing tests followed. Surface and cross-sections analyses were performed by FIB/FEG-SEM, SEM/EDS and micro-Raman spectroscopy. The protective efficiency of a coating based on 3-mercapto-propyl-trimethoxy-silane was also quantitatively assessed by GF-AAS through analysis of metal release, while the aesthetical appearance of coated and uncoated gilded bronze before and after ageing was evaluated by colour measurements.